2022
DOI: 10.1002/ps.7183
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously applied melatonin alleviates the damage in cucumber plants caused by Aphis goosypii through altering the insect behavior and inducing host plant resistance

Abstract: BACKGROUND Aphis gossypii Glover is the main pest found in most cucumber‐producing areas. Melatonin (MT) has been widely studied in protecting plants from environmental stresses and pathogens. However, little knowledge is available on the impact of MT on insect resistance. RESULTS The fecundity of aphids on MT‐treated cucumber leaves was inhibited. Interestingly, MT‐treated plants were more attractive to aphids, which would prevent the large‐scale transmission of viruses caused by the random movement of aphids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…Our results agree with those of Liu et al . (2022), who revealed that MT could inhibit aphid reproduction and mitigate aphid damage to cucumber ( Cucumis sativus L.) plants. Moreover, our results support the previous studies which demonstrated the key role of MT, GB and ALA in controlling bacterial and fungal pathogens (Lavanya and Amruthesh, 2017; Wei et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results agree with those of Liu et al . (2022), who revealed that MT could inhibit aphid reproduction and mitigate aphid damage to cucumber ( Cucumis sativus L.) plants. Moreover, our results support the previous studies which demonstrated the key role of MT, GB and ALA in controlling bacterial and fungal pathogens (Lavanya and Amruthesh, 2017; Wei et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are in harmony with the recent findings of Liu et al . (2022), who recorded elevated flavonoid content in MT‐treated cucumber plants infested with Aphis gossypii Glove.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations